Medical Faculty Members' Spiritual Intelligence/Quotient (SQ): A Descriptive Cross-sectional Study in Iran - Maryam Akbari Lakeh; Hossein Karimi Moonaghi; Abbas Makarem; Habib Allah Esmaieli; Mahdi Ebrahimi (Tabriz University of Medical Sciences, 2013)
Introduction: Recently, promotion of SQ has been introduced as a factor in improving the quality of working life and performance of employees. Since faculty members are the greatest resource of universities; recognition of the SQ and its effectiveness would be the shortcut route to improve their overall performance. Finding and applying all factors affecting the educational organizations promotion is the main approach in improving the quality of higher education. This study aimed to determine the demographic of faculty members, the level of spiritual intelligence and its dimensions in medical faculty members. Methods: This descriptive cross-sectional study with the participant of 160 medical faculty members (32 basic science faculty members, 128 clinical science faculty members) conducted through stratified probability sampling in one of the medical universities in Iran. King's modified Spiritual intelligence questionnaire was used. The data were analyzed using SPSS 11.0. Results: The mean score of faculty members' SQ was 63.0±1.2, which was moderate. There was no significant difference between faculty members' SQ scores (p=0.7) considering the minimum score of 28.0 and maximum score of 87.0; (t=0.4). In dimensions of SQ: the highest score was for critical existential thinking and the lowest one was for transcendental awareness. There was significant difference between dimensions of SQ among the participants (p<0.001). Conclusion: Since we found a significant difference between dimensions of SQ among participants, the studies exploring the nature of this difference were warranted. It seems that proper training for promotion of SQ can be an important step for the development of universities educational organization.